2019
DOI: 10.1097/ajp.0000000000000750
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Individualized Evaluation of Pediatric Abdominal Pain Using Ecological Momentary Assessment (EMA)

Abstract: Objective: The current study aimed to determine if it was feasible and acceptable to use ecological momentary assessment to assess individual associations between biopsychosocial contributors to chronic abdominal pain with 2 objective sensors and a mobile application. Specifically, we aimed to determine if it was possible to identify individualized associations between idiopathic pain associations. The goal was to determine if idiographic profiles have clinical value while the field works torward c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…During recruitment, N = 185 individuals were assessed for eligibility, N = 142 were eligible and approached for the study, N = 79 individuals indicated that they would like to consent and participate in the study, and N = 71 completed the data collection period. The current study was conducted as part of a larger study that examined associations between biopsychosocial factors and abdominal pain [see Cushing et al 9 for more information on the larger study protocol).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…During recruitment, N = 185 individuals were assessed for eligibility, N = 142 were eligible and approached for the study, N = 79 individuals indicated that they would like to consent and participate in the study, and N = 71 completed the data collection period. The current study was conducted as part of a larger study that examined associations between biopsychosocial factors and abdominal pain [see Cushing et al 9 for more information on the larger study protocol).…”
Section: Participantsmentioning
confidence: 99%
“…Findings indicated that pediatric pain patients found this protocol to be highly feasible and acceptable. 9 Given the many potential points of intervention for youth with chronic pain, narrowing the field to those points most important to a given patient's pain process may serve to decrease treatment burden and increase adherence to the interventions prescribed. Future interventions could consider a similar baseline data collection period to inform tailored pediatric pain interventions related to Fear Avoidance variables.…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric abdominal pain has also been evaluated by means of accelerometry through the assessment of the sleep and physical activity [172]. The relationship between self-scored pain, muscular activity and postural load during cleaning activities was studied in [173], and the authors found a higher muscular activity in the case of low-level pain compared to subjects reporting a higher level of pain.…”
Section: Physical Activity As a Pain Indexmentioning
confidence: 99%
“…In conclusion, objective sensor-based pain monitoring technologies have the potential to help improving the patient's quality of life [312], to understand better the pain biopsychosocial processes and may be of interest in the study of other related conditions [172]. Funding: This work was supported in part by the "Fondo de Investigaciones Sanitarias" (Instituto de Salud Carlos III, Spain) under Grants PI15/00306, in part by the "Fundación Progreso y Salud" (Government of Andalucía, Spain) under Grant PIN-0394-2017, in part by "Fundación Mutua Madrileña" under grant VÍA-RENAL, and in part by the "Eurostars Programme", European Commission, under Grant "FRAIL".…”
Section: Future Trends and Conclusionmentioning
confidence: 99%